Proces doskonalenia się instrumentarium badawczego nauk laboratoryjnych - Kazibut, Radosław (Biuro Upowszechniania i Promocji Nauki PAN, 2012)
Process of improvement of the research instrumentation in the laboratory sciences In the article I invoke characterizations of the structure of laboratory sciences proposed by Ian Hacking. I will expand his argument about the “self-vindication” of the laboratory sciences and show that the present aspect of this practice is a result of the improvement process in the research instrumentation of these sciences. In the history of the laboratory sciences one can notice the process of evolutional increasing of standards in laboratory works and of creating continuously improving research instrumentation. In support of my argument I analyze the four stages of the development of the laboratory sciences research instruments: alchemists’ works, Boyle’s laboratory works, Lavoisier’s laboratory practice and the laboratory sciences after the instrumentation revolution. Key words: philosophy of natural science, laboratory science, laboratory style
Keywords: nauki laboratoryjne; paralaboratorium; protolaboratorium; laboratorium; alchemia; Robert Boyle; Lavoisier; rewolucja naukowa